Improved overall survival in head and neck cancer patients after specific therapy of distant metastases - Schulz, Dominik; Wirth, Markus; Piontek, Guido; Knopf, Andreas; Straube, Christoph; Pigorsch, Steffi; Combs, Stephanie E.; Pickhard, Anja (European Archives of Oto-Rhino-Laryngology, 2018)
Purpose: While metastases directed therapy for oligometastatic disease is recommended in different cancer entities, the treatment of solitary metastases in head and neck squamous cell carcinoma (HNSCC) patients is not clearly defined. Methods: A retrospective analysis was performed on data from 143 HNSCC patients treated between 2001 and 2016 in a tertiary university hospital. Clinical factors and outcome were measured using the median survival of patients receiving metastases specific therapy in comparison with matched control patients. Results: In 37 patients, distant metastases were treated specifically with either surgery and/or stereotactic ablative radiotherapy and had with 23.97 months a more than three times higher median survival than 10 untreated matched controls with potentially treatable distant metastases (7.07 months). Conclusions: Our retrospective analysis demonstrates a significant survival benefit for HNSCC patients who received a specific therapy regarding distant metastasis irrespective of localization as compared to a matched control cohort.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Distant metastases; HNSCC; Overall survival; Radiotherapy; Specific treatment